Luteolin Pretreatment Ameliorates Myocardial Ischemia/Reperfusion Injury by lncRNA-JPX/miR-146b Axis - Tongda Xu; Yuanyuan Zhang; Gege Liao; Haochen Xuan; Jie Yin; Jieli Bao; Yang Liu; Dongye Li (Analytical Cellular Pathology)
Background. In the present study, we aimed to find out whether luteolin (Lut) pretreatment could ameliorate myocardial ischemia/reperfusion (I/R) injury by regulating the lncRNA just proximal to XIST (JPX)/microRNA-146b (miR-146b) axis. Methods. We established the models in vitro (HL-1 cells) and in vivo (C57BL/6J mice) to certify the protection mechanism of Lut pretreatment on myocardial I/R injury. Dual luciferase reporter gene assay was utilized for validating that JPX could bind to miR-146b. JPX and miR-146b expression levels were determined by RT-qPCR. Western blot was utilized to examine apoptosis-related protein expression levels, including cleaved caspase-9, caspase-9, cleaved caspase-3, caspase-3, Bcl-2, Bax, and BAG-1. Apoptosis was analyzed by Annexin V-APC/7-AAD dualstaining, Hoechst 33342 staining, as well as flow cytometry. Animal echocardiography was used to measure cardiac function (ejection fraction (EF) and fractional shortening (FS) indicators). Results. miR-146b was demonstrated to bind and recognize the JPX sequence site by dual luciferase reporter gene assay. The expression level of miR-146b was corroborated to be enhanced by H/R using RT-qPCR (P<0.001 vs. Con). Moreover, JPX could reduce the expression of miR-146b, whereas inhibiting JPX could reverse the alteration (P<0.001 vs. H/R, respectively). Western blot analysis demonstrated that Lut pretreatment increased BAG-1 expression level and Bcl-2/Bax ratio, but diminished the ratio of cleaved caspase 9/caspase 9 and cleaved caspase 3/caspase 3 (P<0.001 vs. H/R, respectively). Moreover, the cell apoptosis change trend, measured by Annexin V-APC/7-AAD dualstaining, Hoechst 33342 staining, along with flow cytometry, was consistent with that of apoptosis-related proteins. Furthermore, pretreatment with Lut improved cardiac function (EF and FS) (P<0.001 vs. I/R, respectively), as indicated in animal echocardiography. Conclusion. Our results demonstrated that in vitro and in vivo, Lut pretreatment inhibited apoptosis via the JPX/miR-146b axis, ultimately improving myocardial I/R injury.